THE CORRELATION BETWEEN THE APPLICATION OF THE COOPERATIVE TEACHING MODEL AND MULTIMEDIA LEARNING MEDIUM WITH STUDENTS' INTEREST IN LEARNING THE ISLAMIC RELIGION EDUCATION SUBJECT AT SMA NEGERI 1 CIGUDEG - Purwanto Purwanto; Akhmad Alim; A. Rahmat Rosyadi (Program Studi Magister Pendidikan Agama Islam, Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2018)
A problem often encountered in teaching Islamic Religion Education at school is the students' boredom in following the learning activities and the low motivation in learning Islamic Religion Education. Some of this is because of the monotonous teaching methodology and the learning media in the learning process. This study was aimed to discover the relationship between the application of a cooperative learning model and multimedia learning medium and the students' interest in learning the Islamic Religion Education Subject at SMA Negeri 1 Cigudeg. This study used a quantitative approach with a correlational research method. The data were collected using observation, interview, and questionnaire techniques. The data analysis technique used was a quantitative technique with assistance from the Microsoft Office Excel and SPSS 20 software. Keywords : Cooperative Learning Model, Multimedia Learning Medium, Student's Interest in Learning